Pengaruh Kepemimpinan dan Motivasi terhadap Disiplin Kerja Karyawan pada Koperasi Keluarga Besar PT. Semen Padang (KKSP) - Sarianti, Rini; Firman, Firman; Roseani, Yoska (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2013)
The aims of this research are to analyze (1) The influence of leadership toward motivation (2) The influence of leadership and motivation toward discipline of work. The type of this research belongs to descriptive causative research. Population used for this research was 65 people. The technique used for the sample is Proportional Stratified Random Sampling which taken based on the level of education where this sample was 56 people. Primary data taken from questioner distribution toward respondent, then secondary data taken from the data, which is correlated to the research given by Koperasi Keluarga Besar Semen Padang. Technique analysis used for this research is path analysis with SPSS program version 16. The results of this research show that (1) There is no significant relationship between leadership and motivation. (2) There is significant relationship between leadership and discipline of work. (3) There is significant relationship between motivation and discipline of work.Based on research and resume, so it is suggested to the chief to notice the leadership aspect, motivation and increase the discipline of work to Koperasi Keluarga Besar Semen Padang employee to reach the goals of the company.